Nebulous Boundaries: Geographies of Identity in El hombre del acordeón - Julie A Sellers (Studies in 20th & 21st Century Literature, 2015)
Boundaries are never as definitive as they appear at first glance, for they create a broader zone, the borderlands, where the people, practices, and products from both sides comingle. Despite boundaries' demarcating intent, the borderlands they cross are a syncretic blend of the lands on each side. The borderland as fictional setting draws our attention not to the fixedness of boundaries, but rather to their flexibility. Set in the Dominican-Haitian borderland, Marcio Veloz Maggiolo's El hombre del acordeón ('The Accordion Man') draws upon the dynamism of that geopolitical border to call into question other apparently definitive boundaries, thus challenging official religious, racial, and musical discourses of Dominicanness.
Keywords: Marcio Veloz Maggiolo; merengue; Dominican Republic; borderlands; Vodou; Rafael Trujillo